BeeHide JPEG steganography using Artificial Bee Colony algorithm - Caandi, Jeston Alwin O.; Tarrayo, Ma. Emily A. (2010)
Steganography is an art of concealing information within a cover image making it undetectable under usual conditions. In this paper, we proposed a new scheme of steganography that is based on JPEG and Artificial Bee Colony algorithm (ABC). Using the ABC algorithm, an optimal substitution matrix that will evenly distribute the secret data obtained, that is, finding a substituttion matrix that will evenly distribute the secret data within the cover image. Moreover, in Joint Photographic Experts Group (JPEG) image compression, an image can hold more secret messages by modifying the standard luminance and chrominance JPEG quantization tables. In this proposed approach, the cover image is processed to prepare it hold the secret data by applying Discrete Cosine Transformation (DCT) and Quantization procedures and then the resulting ABC substituted secret data is embedded tothe quantized DCT coefficients of the cover image in its DC-to-middle frequency components producing a stego-image. Experimental results show that the proposed method has a large embedding capacity and the resulting stego-image is visually impossible to differentiate from the original cover image.